Effect of Assembly Errors on Ground Tooth Surface Deviations for Large-Scale CNC Gear Profile Grinding Machines - Wenzheng Ding; Wenquan He; Hu Zhang; Yao Li (Machines, 2022)
Assembling plays a significant role in the performance of large-scale CNC gear profile grinding machines. An approach in the deviation evaluation of ground tooth surfaces taking into account assembly errors is proposed in this paper. Based on the error transmission chain of the profile grinding system and the conjugate motion relationship between the grinding wheel and the workpiece, the ground tooth surface model including assembly errors was established using the surface envelope method. Then, the effect of assembly errors on deviations of the profile grinding tooth surface was quantitatively analyzed. The optimized distribution of assembly errors and machining verifications were performed on large-scale CNC gear profile grinding machines. The results show that the proposed method is effective at ensuring ground tooth surface deviations for large-scale CNC gear profile grinding machines.